Application of KLE-PEM for Random Dynamic Analysis of Nonlinear Train-Track-Bridge System - Lizhong Jiang; Xiang Liu; Tuo Zhou; Ping Xiang; Yuanjun Chen; Yulin Feng; Zhipeng Lai; Shanshan Cao (Shock and Vibration)
A nonlinear train-track-bridge system (TTBS) considering the random track irregularity and mass of train is discussed. Based on the Karhunen–Loéve theory, the track irregularity is expressed and input into the TTBS, and the result of random response is calculated using the point estimation method. Two cases are used to compare and validate the applicability of the proposed method, which show that the proposed method has a high precision and efficiency. Then, taking a 7-span bridge and a high-speed train as an example, the calculation results of random response of the nonlinear and linear wheel-rail model are compared, and the results show that for the bridge and rail response, the nonlinear and linear models are almost the same. Finally, comparing the calculated probability distribution results with the test results, it shows that the method can be applied to the prediction of actual response range.